A construção da identidade de marca de Gramado-RS como "destino turístico modelo" - Azambuja, Vanessa Acosta de (My University, 2015)
Gramado-RS has the image of "tourist destination model" between the Ministry of Tourism and other institutions in the area, other Brazilian and international destinations, and tourists. From this statement and considering the brand image as a concept related to the receiver, while brand identity as a concept associated with the issuer, this research has the problem question: How the Gramado’s brand identity is built to generate the "tourist destination model" image? In the theoretical reference are studies found about overall brand identity and tourist destinations brand identity. Among the theoretical models covered in these studies, the Hankinson’s model (2004) was selected, entitled "The relational network brand", to reach the goal of this research: to characterize the Gramado’s brand identity built to instill the image of "tourist destination model". Organizational and analytical procedures of discursive data is guided by assumptions and techniques of content analysis. The research universe was integrated by subjects of the government, the private sector, workers and the local community of Gramado, a total of 21 respondents. In addition to interviews, being a case study, were also consulted books about the history of tourism in Gramado; dissertations of Tourism and Hospitality Master in UCS that this destination is the study scenario; and reports connected with the research. Among the results is that the attributes with the highest occurrence in the answers of respondents were symbolic and functional attributes, especially "tourist attraction/events" as what differentiates Gramado from your competitors. The relationship between the brand and tourists is based more in this destination be considered conducive to leisure, attractive, innovative and it has credibility. Also, it was evidenced a lack of strategic planning with the active participation of internal stakeholders. As for relationships with other stakeholders, it was found that practically does not use paid advertising.
Gramado-RS tem a imagem de “destino turístico modelo” para o Ministério do Turismo e outras instituições da área, outros destinos brasileiros e internacionais, e turistas. Partindo dessa assertiva e considerando a imagem de marca como um conceito relacionado com o receptor, enquanto a identidade de marca como um conceito associado ao emissor, esta pesquisa tem como questão-problema: Como é construída a identidade de marca de Gramado, para gerar a imagem de “destino turístico modelo”? No referencial teórico, encontram-se estudos sobre identidade de marca geral e de destinações turísticas. Dentre os modelos teóricos abordados nesses estudos, foi selecionado o modelo de Hankinson (2004), intitulado “A rede relacional da marca”, para se chegar ao objetivo desta pesquisa: caracterizar a identidade de marca de Gramado construída para gerar a imagem de “destino turístico modelo”. Os procedimentos organizativos e analíticos dos dados discursivos pautaram-se por supostos e técnicas da análise de conteúdo. Integraram o universo da pesquisa sujeitos do Poder Público, da iniciativa privada, dos trabalhadores e da comunidade local de Gramado, totalizando 21 entrevistados. Além de entrevistas, como um estudo de caso, também foram consultados livros sobre a história do turismo em Gramado; dissertações do Mestrado em Turismo e Hospitalidade da UCS, em que essa destinação é o cenário de estudo; e reportagens afetas à pesquisa. Dentre os resultados está que os atributos, com maior ocorrência nas respostas dos entrevistados, foram os simbólicos e os funcionais, destacando-se atrativos/eventos turísticos, como aquilo que diferencia Gramado de seus concorrentes. O relacionamento entre a marca e os turistas baseia-se mais em essa destinação ser considerada propícia ao lazer, atrativa, inovadora e de credibilidade. Também foi constatada a falta de um planejamento estratégico com a participação ativa dos stakeholders internos. Quanto aos relacionamentos com outros stakeholders, foi verificado que, praticamente, não se utiliza publicidade paga.
Keywords: Turismo - Gramado (RS); Turismo - Marketing; Publicidade - Gramado (RS); Tourist trade - Gramado (Brazil); Tourism - Marketing; Publicity - Gramado (Brazil)